The use of fish pond water for growing Chlorella sp. In Other Places - Febryanti, Esra; Dahril, Tengku; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Fish pond water is rich in micro and macro nutrients originated from feces and fish feed remains and it may be used to grow the microalgae such as Chlorella sp. A study to understand the growth of Chlorella sp in the pond water media and the amount of nutrient used was conducted from January – March 2016. The Chlorella sp. was grown indoor and outdoor. Parameters measured were Chlorella sp. biomass, nitrate and phosphate content. Samplings were conducted once/10 days. Results shown that Chlorella sp. grow well in the pond water. The biomass of indoor Chlorella sp. was higher than that of the outdoor (0.005 g/L and 0.003 g/L respectively). Nitrate and phosphate content was decreased during the experiment, the nitrate was reduced by 7.4 mg/L (indoor) and 9.4 mg/L (outdoor), while the phosphate was reduced by 0.09 mg/L (indoor) and 0.26 mg/L (outdoor). Based on data obtained that the waste can be used to grow microalgae Chlorella sp. Keywords: Fish pond water, Chlorella sp., indoor, outdoor